SISTEM INFORMASI AKUNTANSI PEMBERIAN KREDIT DENGAN MENERAPKAN PERHITUNGAN BUNGA FLAT PADA KSP DAHLIA BOJA - Munifah; Yasar Wicaksono Reform (LPPM Politeknik Pratama, 2021)
This research is a development research that aims to design and build a web-based credit lending accounting information system that can meet user needs in terms of managing data and information related to loan applications and installments by applying flat interest calculations and the 5C of credit method as an assessment guide. This research and development data collection was carried out by collecting data and information on KSP Dahlia Boja, conducting interviews with application users and studying literature. This web-based credit lending accounting information system was built using Visual Studio Code and PhpMyAdmin software as databases. This research resulted in a web-based credit lending accounting information system that is integrated with a database, which provides access to every user to be able to process data collection, transactions, assessments, and reporting related to credit distribution to installments based on validation tests and blackbox testing.